The nasal index in brazilian human skeletons - Larissa Chaves Cardoso Fernandes; Marcus Vitor Diniz de Carvalho; Eduardo Daruge Júnior; Luiz Francesquini Júnior; Patrícia Moreira Rabello; Evelyne Pessoa Soriano (Universidade Estadual de Campinas, 2018)
Aim: To investigate the percentage of correctness (PC) of the Nasal Index (NI) in human skeletons for determination of sex, ancestry and estimation of age in the Brazilian population. Methods: This was a cross-sectional study of 173 human skulls belonging to the Piracicaba Dental School. 93 skeletons were males and 80 females; 34 were aged up to 39 years, 56 between 40 and 59 years, and 83 60 years or older; 96 were from white individuals, 49 were from mixed-race and 28 from black individuals. High-precision digital caliper was used to measure nasal height (NH=ANS-nasion) and the maximum nasal width (NW) values, which were applied into the formula NI=NW/NHx100. The data were submitted to discriminant analysis and Student's t test with equal variances, Mann-Whitney, F (ANOVA), Tukey and Kruskal Wallis, 5% significance level. Results: Dominant nasal type in the Brazilian population was the mesorine. Males showed nasal height and width values greater than those of females, with statistically significant differences in all measurements (p≤0.021) and PC of 76.6%. Similar nasal measurements were found regardless of age (p>0.05), with PC of 41.7%. Ancestral analysis revealed that black individuals have greater nasal width (26.35) and nasal index (53.67) than white ones (24.60 and 49.25), while mixed-race individuals showed intermediate values (25.36 and 52.13) (p<0.05). Nevertheless, these measurements presented an estimated PC of 54.3%. Conclusion: The Nasal Index can be better used for sex determination than for estimation of age and ancestry in the Brazilian population, as the latter showed intermediate and low percentage of correctness, respectively.